The Role of Social Media and Motivation on Students’ Interest in Entrepreneurship with Self-Efficacy as an Intervening Variable - Effendi, Nur Ika; Rika Sandi, Wahyu Faisa; Anroni, Yopi Eka; Amran, Amran (Universitas Muhammadiyah Magelang, 2025)
Digitalization has changed the way students access information and ultimately shapes their interest in entrepreneurship by utilizing social media. This study aims to investigate the impact of social media and motivation on students' interest in entrepreneurship, with self-efficacy serving as an intervening variable among students at Muara Bungo University. This research employs a quantitative method with a sample of 101 students selected through proportionate stratified random sampling. Based on the Smart-PLS 4 data statistical tool, the study found that social media, motivation, and self-efficacy have a positive and significant effect on interest in entrepreneurship partially. Self-efficacy has been proven to fully mediate the relationship between social media and motivation for those interested in entrepreneurship. Hopefully that universities, such as the University of Muara Bungo, will enhance the efficacy of developing programs and utilize social media as a tool for learning and motivation. This approach can help increase students' interest in entrepreneurship to create jobs and contribute to economic growth in Bungo Regency